2020
DOI: 10.5696/2156-9614-10.26.200603
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality and Pollution Index for Heavy Metals in Saïs Plain, Morocco

Abstract: Background. Heavy metals contamination threatens groundwater resources in many areas around the world. Various methods to evaluate groundwater quality have been used to characterize sources of contamination and associated parameters. For assessment of heavy metals contamination, calculation of pollution indices is an effective tool for assessing water quality. Objectives. The purpose of the present study was to assess heavy metal concentrations and determine distributions in Saïs plain, Morocco using multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The study by Khan et al in India showed that Fe was a dominant contaminant in groundwater [35]. Due to the natural existence of Fe in the environment, the enrichment of Fe can be related to untreated wastewater from residential areas, industrial sites and agricultural activities [36]. Moreover, using agecorroded pipes in groundwater extraction is also a common source of Fe [35].…”
Section: Figure 3 Boxplots Of Groundwater Quality Parameters In the M...mentioning
confidence: 99%
“…The study by Khan et al in India showed that Fe was a dominant contaminant in groundwater [35]. Due to the natural existence of Fe in the environment, the enrichment of Fe can be related to untreated wastewater from residential areas, industrial sites and agricultural activities [36]. Moreover, using agecorroded pipes in groundwater extraction is also a common source of Fe [35].…”
Section: Figure 3 Boxplots Of Groundwater Quality Parameters In the M...mentioning
confidence: 99%
“…European Union has recommended the levels of 0.2 mg/L and 0.05 mg/L for Fe and Mn, respectively (EU, 1998). Groundwater contamination by trace metals, particularly Fe, As, and Mn, has been existed globally, which occurred naturally or associated with anthropogenic activities (Lotfi et al, 2020;Malakootian et al, 2020). In the western Nile Delta region of Egypt, groundwater from 108 wells was examined for trace metals.…”
Section: Introductionmentioning
confidence: 99%
“…The permissible values were sourced from the ZABS standard ( ZABS 2010 ). The maximum allowable concentration and highest desirable values were adopted from ( Lotfi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%